The Influence of Perceived Risk and Perceived Enjoyment on Repurchase Decision in the Honda Service Application (Study on BromPit Users at AHASS Blimbing, Malang) - Cahya Fayyaza; Asminah Rachmi; Mohammad Maskan (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
The intense competition in the after-sales motor vehicle service industry encouraged companies to innovate through service digitalization. One of the innovations is the BromPit application developed by Honda to facilitate the vehicle service booking process. However, the successful adoption of this application is still influenced by several factors, including perceived risk and perceived enjoyment. This study is to examine the influence of perceived risk and perceived enjoyment on repurchase decision among BromPit application users at AHASS Blimbing, Malang City.This research employed a quantitative approach. The sample consisted of 55 respondents who were active users of the BromPit application, selected using purposive sampling. The data were processed using multiple linear regression analysis and hypothesis testing.The regression analysis showed that perceived risk and perceived enjoyment partially had a positive and significant effect on repurchase decision. Meanwhile, the regression result confirmed that both variables also had a positive and significant simultaneous effect on the repurchase decision.These findings concluded that the lower the perceived risk and the higher the level of enjoyment when using the BromPit application, the greater the tendency for users to make repeat purchases of services through the digital platform.